2008
DOI: 10.1007/s00464-008-0196-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary and overall success rates for clinical outcomes after laparoscopic, endoscopic, and open pancreatic cystgastrostomy for pancreatic pseudocysts

Abstract: Laparoscopic and open pancreatic cystgastrostomy both have a higher primary success rate than endoscopic internal drainage, although repeat endoscopic cystgastrostomy provides overall success for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 15 publications
3
97
0
1
Order By: Relevance
“…Although there is a lack of evidence, endoscopic drainage may be preferred to surgical treatment because it has a better risk/benefit profile, being less invasive and providing an equally effective drainage, and it is the treatment of choice in high-risk patients [215,216]. Moreover, endoscopy does not exclude or compromise subsequent surgery.…”
Section: E3: Is Endoscopic Therapy Indicated In Chronic Pancreatitismentioning
confidence: 99%
“…Although there is a lack of evidence, endoscopic drainage may be preferred to surgical treatment because it has a better risk/benefit profile, being less invasive and providing an equally effective drainage, and it is the treatment of choice in high-risk patients [215,216]. Moreover, endoscopy does not exclude or compromise subsequent surgery.…”
Section: E3: Is Endoscopic Therapy Indicated In Chronic Pancreatitismentioning
confidence: 99%
“…10 With the advent of laparoscopy drainage of the pancreatic pseudocyst by laparoscope began. 6,8,9,11 Up to 2016 more than 250 laparoscopic drainage procedures for pancreatic pseudocyst were performed worldwide with mortality rate 0% success rate 92%, overall complication rate 9%,6.7% conversion to open surgery and recurrence rate 3%.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It is reported that conventional open technique had morbidity rate can reach up to 40% and a mortality rate in 5.8%. 5 due to high morbidity and mortality rate the introduction of minimal invasive surgery for pancreatic pseudocyst was developed in 1990 this include laparoscopic internal drainage of the pseudocyst, endoscopic drainage and radiological drainage techniques.…”
mentioning
confidence: 99%
“…The success rate is reportedly about 77%, and the mortality rate is about 11%. The main complications include pancreatic fistula formation, abdominal infection, and retroperitoneal infection [14]. With respect to the optimal timing of surgery, it is advisable to wait until 4 weeks after the onset of pancreatitis if possible.…”
Section: Cmentioning
confidence: 99%